Implementation of Environmental Accounting Policies in Hospitality Business in an Effort to Improve Tourism Sustainability in the Lake Toba Region - Tamba, Dang Panagaman; Marpaung, Durahman (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The Lake Toba area is an iconic tourist destination in Indonesia that faces major challenges in preserving its ecosystem. Stakeholders, especially hotel companies, need to be able to develop more effective strategies to achieve sustainable tourism in the Lake Toba area. The aim of this research is to find out the relationship between hotel companies' environmental accounting policies and driving factors, including hotel companies' corporate social responsibility (CSR) programmes, management support and community support. The research method used in this research is mixed method research (qualitative and quantitative). Analysis of qualitative data processing using Nvivo. Then, quantitative analysis using data analysis methods, namely by testing questionnaires, validity, reliability, data normality, multicollinearity, heteroscedasticity, multiple regression analysis, and testing the coefficient of determination of the best fit model. The results of the qualitative research with Nvivo based on the concept of tourism sustainability are CSR, environmental issues, public image and environmental accounting policies. The results of the quantitative research based on the partial test showed that CSR and management support had a significant effect on the accounting policy of the hotel business environment, while the community support variable had no effect on the accounting policy of the hotel business environment.